A retrospective study of in hospital time management of acute stroke patient in the emergency department Hospital Kuala Lumpur - Norzilah, Abu Zaharin (2008)
The Emergency Department Hospital Kuala Lumpur commonly receives cases of patients presented with signs and symptoms of acute stroke in which majority of them are send for CT Brain for confirmation of diagnosis. However in a case of acute ischaemic stroke none of them had been given fibrinolytic therapy or r-tpa in which assumption made that the patient had missed the beneficial period of the therapy which is within 3 hours from the onset of symptoms. The objectives of the study are to analyse the in-hospital time taken for stroke patients when arrives in the Emergency Department until the diagnosis of stroke is confirmed. This will include the time interval from door to medical consultation,door to CT scan performed till door to CT scan film interpreted.Besides this the time of symptoms onset is also studied as well as the demographic profile of the stroke patients. The association between the demographic factor and stroke risk factors with the time of hospital arrival is also include in the study. A total of 200 patients were involved in the study. All subjects were those age more than 18 years old who presented to the emergency department with the signs and symptoms of acute stroke and had CT brain done.The data analyse will be collected retrospectively through case notes in which the detail of the patients, demographic factor, history of presenting complaint, past medical history, social history, time documentation when seen by doctor till CT film interpretation will be reviewed. In this study the data analysed are stroke patients presented to the Emergency Department Hospital Kuala Lumpur in a period of 1 year from 1st April 2007 until 31st March 2008 From 200 patients 42% of them are Malay followed by Chinese (36.5%), Indian (18.5%) and others (3.0%). Male accounted for 65% while female accounted for 35%. The mean age was 58.3 years old with 58.5% were more than 55 years old. The CT brain finding shows infarct in 42.5% of patients, normal CT finding accounted for 39% and haemorrhagic stroke in 18.5% of patients. The percentage of patients who arrived more than 3 hours from the onset of symptoms was 73% while less than 3 hours was 27% . Most of the patient is triaged to the yellow zone which accounted for 45.5%, followed by the green zone which is 41.5% and the red zone (13%) . As for the in-hospital time analysis, it is found that the mean time interval for door to medical consultation is 24.2 minutes and the mean time interval for door to CT is 52.3 minutes. Hypertension occurs highest most among the patients (52.5%) followed by diabetes (41.5%),family history of stroke (23%), smoking (21%), ischaemic heart disease (14.5%), previous history of stroke (8%) and hyperlipidaemia (3.5%). There is a significant association between time of hospital arrival and age in which pvalue is less than 0.05. The significant independent predictors for time of hospital arrival is age (OR 1.83,95% CI 0.958,3.502), Hypertension (OR 1.99,95% CI 0.989,3.906) and ischaemic heart disease (OR 0.424,95%CI 0.174,1.036). 73% of stroke patients arrives late to the Emergency Department Hospital Kuala Lumpur. There is also an in-hospital delay in which may jeopardise the chance of patient for fibrinolytic therapy. Critical pathway might need to be structured in the emergency department to overcome the delay, hence improving the care of stroke patient.